3D characterization of brittle fracture zones in Kevitsa open pit excavation, northern Finland - Lindqvist, Teemu (Helsingfors universitet, 2014)
This work aims at delineating the geometry and geotechnical properties of major fracture zones within the Kevitsa open pit excavation in northern Finland. The results are intended to be used as input parameters for a comprehensive slope stability study scheduled for 2014 by Engineering Consulting Group WSP Finland Ltd. The present work has both a regional and local-scale focus. The regional study focuses on identifying major linear trends from topographic and aeromagnetic maps, whereas the local scale study focuses on building 3D fracture zone models by merging lineaments interpreted from detailed digital elevation model and fracture data mapped from open pit mapping, 3D photogrammetry models and borehole videos. The orientation constraints derived from the fracture data are merged with RQD- and RG-logs to build the 3D fracture zone models. The regional topographic lineaments (RTL) comprise two main orientations with NNW-SSE and SSW-NNE trends. The regional aeromagnetic lineaments (RAL) indicate NW-SE and SW-NE orientations. The local topographic lineaments (LTL) indicate NNW-SSE, SSW-NNE, WSW-ENE and NW-SE orientations. Ground surface fracture data mapped from 3D photogrammetry models comprise steeply ENE- and steeply SE-dipping fracture sets. Fracture data derived from borehole videos show steeply ENE-, steeply SE-, sub-horizontally SW- and gently NNE-dipping fracture sets. Furthermore, the open pit mapping observations reveal the presence of gently WNW- and steeply ENE-dipping brittle zones of rock. The main 3D photogrammetry and borehole video fracture sets define wedge shaped blocks of rock at the slopes of the Kevitsa open pit excavation. The studied brittle fractures and fracture zones most probably originate from the general NW-SE oriented compressive stress field in the Finnish bedrock. However, most of the observed fracture sets are not oriented parallel to the compression. Instead, the fracture sets form conjugate shear fracture pairs that are attributed to a transpressive stress field comprising the ...